Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$f(y)\le f(x)$ and $x<y$ where $f$ is convex function and $g$ is increasing convex function.
Then $(1-\lambda)g(\lambda f(x)+(1-\lambda)f(y)) \le (1-\lambda) g(f(y))$.

I can't understand well.
I guess, since $g$ is increasing function,
the inequality should be $(1-\lambda)g(\lambda f(x)+(1-\lambda)f(y)) \le (1-\lambda) g(f(x))$ because $f(y)\le f(x)$.

Why does that inequality hold?

share|cite|improve this question
up vote 0 down vote accepted

The inequality, as you have found out, is not true in general. One can easily construct a counterexample (e.g. $\lambda=\frac12,\, x=0,\, y=1,\, f(t)=1-t,\, g(t)=t$). There must be a typo.

share|cite|improve this answer
Then this is true? : Since $g$ is increasing, $g(f(\lambda x+(1-\lambda)y)) \le g(\lambda f(x)+(1-\lambda)f(y))$. – cowik Dec 14 '12 at 10:44
This is indeed true, since $f$ is convex and $g$ increasing. – Nick Papadopoulos Dec 14 '12 at 10:51
Hmm, this is neither of the two inequalities you mentioned in your question, but it is true anyway. – user1551 Dec 14 '12 at 10:52

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.